Osseous Metaplasia of the Transverse Humeral Ligament in a 10-Year-Old Bengal Cat - Rodiño Tilve, Verónica; Maddox, Thomas; Ressel, Lorenzo; Pettitt, Rob (VCOT Open, 2022)
This report is of an osseous metaplasia of the transverse humeral ligament and secondary bicipital tenosynovitis in a 10-year-old Bengal cat. Computed tomography revealed the presence of an osseous bridge enclosing the bicipital groove, with ultrasonography confirming partial tear and inflammation of the bicipital tendon. Initial conservative management with intra-articular long-acting steroids failed to provide long-term improvement of clinical signs. Surgical excision of the osseous lesion resulted in complete resolution of lameness after surgery, confirmed by a 1-year follow-up. Histopathology of this lesion confirmed a well-differentiated osseous metaplasia of the transverse humeral ligament.
Keywords: bicipital tenosynovitis; shoulder pain; bony exostosis; mineralization; ossification